2017
DOI: 10.1111/lre.12188
|View full text |Cite
|
Sign up to set email alerts
|

Gillnet selectivity estimates for five commercially important fish species in Tono Reservoir, Northern Ghana

Abstract: Gillnet selectivity is crucial for the effective and sustainable management of fisheries. However, there is inadequate information on gillnet selectivity for commercially important species in Tono Reservoir. To facilitate the sustainable exploitation of fish species, this study was conducted to estimate the selectivity parameters of commonly used monofilament gillnets for commercially important fish species in Tono Reservoir from January 2015 to June 2016. Two common nylon monofilament gillnets used by fisherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The desirable target would be to let as many fish as possible spawn at least once before they are caught, to rebuild and maintain healthy spawning stocks (Froese 2004). The total length at first sexual maturity was based on published research on the species (Adite and Van Thielen 1995, Akongyuure et al 2017b, Duponchelle and Panfili 1998, Kwarfo-Apegyah and Ofori-Danson 2010, Lederoun et al 2016, Ofori-Danson et al 2008.…”
Section: Relative Yield Per Recruit (Y'/r) and Reference Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The desirable target would be to let as many fish as possible spawn at least once before they are caught, to rebuild and maintain healthy spawning stocks (Froese 2004). The total length at first sexual maturity was based on published research on the species (Adite and Van Thielen 1995, Akongyuure et al 2017b, Duponchelle and Panfili 1998, Kwarfo-Apegyah and Ofori-Danson 2010, Lederoun et al 2016, Ofori-Danson et al 2008.…”
Section: Relative Yield Per Recruit (Y'/r) and Reference Pointsmentioning
confidence: 99%
“…Research has mainly focused on fisheries socioeconomics, water productivity, sedimentation, and water storage, in particular at Tono (Abache 2015, Abubakari 2015, Diekkr€ uger and Liebe 2002, Mdemu 2008, Okrah 2010. Recent work on the Tono Reservoir by Akongyuure et al (2017b) was focused on gillnet selectivity estimates of the target fish species. Kwarfo-Apegyah (2008) studied the exploitation rates and management implications of the Bontanga Reservoir fisheries from 2004 to 2006 and reported that the reservoir had 26 fish species belonging to 19 genera in 11 families.…”
mentioning
confidence: 99%
“…The optimum total lengths at capture of four of these fish species excluding C. zillii ranged from 13.53 to 25.43 cm using a 5‐centimeter (cm) gillnet and 18.95–35.60 cm using a 7‐cm gillnet. The mean total length at first sexual maturity for all five fish species ranged from 8.60 to 28.86 cm (Akongyuure, Amisah, & Agyemang, ).…”
Section: Methodsmentioning
confidence: 99%
“…The fishermen usually use the gill nets for catching little tuna, Indian mackerel, scad, sardines and other pelagic fishes. The gill nets are considered as environmentally friendly fishing gears and research on this gear continuous to be developed [1,[18][19][20][21]. The catch is usually directly marketed in the form of fresh fish.…”
Section: Characteristic Of Respondentsmentioning
confidence: 99%